Aorto-enteric Fistula 15 Years After Uncomplicated Endovascular Aortic Repair with Unforeseen Onset of Endocarditis. (2016) - Kadhim, M.M.K.; Rasmussen, J.B.G.; Eiberg, J.P.
Abstract : Introduction: Aorto-enteric fistula after endovascular aortic repair is an exceedingly rare but serious condition. Report: A rare case of a fistula between the excluded aortic sac and the transverse colon 15 years after endovascular aortic repair is described. Onset was endocarditis without gastrointestinal haemorrhage, migration, endoleak, or aortic sac dilatation. The patient was successfully treated by fistula excision, debridement and broad spectrum antibiotic treatment without endograft explantation. Discussion: Aorto-enteric fistula can emerge after endovascular repair with an unforeseen onset such as endocarditis, which in this case probably occurred as metastatic sepsis from endograft infection. Highlights: Uneventful endovascular aneurysm repair can generate an aorto-enteric fistula to a successful excluded and stable aneurysm sac. This case underlines the need for awareness of unusual symptoms that could represent potential late EVAR related complications. A conservative approach without graft removal seems feasible in this case with severe comorbidity.